EFFECT OF EDTA AND 3.8% SODIUM CITRATE ON BLOOD SEDIMENTATION RATE BY WESTERGREN METHOD WITH 0.86% NACL - Rahmayani Agustin Nanda Kusuma; Emma Ismawatie; Yulia Ratna Dewi (Tahta Media Group, 2025)
Background: The erythrocyte sedimentation rate (ESR) is a hematological test used to detect inflammatory processes and blood disorders. ESR values can be influenced by the type of anticoagulant used. Objective: To compare ESR values in venous blood samples using EDTA and 3.8% sodium citrate anticoagulants with the Westergren method modified by the addition of 0.86% NaCl. Methods: This study employed an observational analytical approach with a cross-sectional design, conducted at the Clinical Pathology Laboratory of Politeknik Indonusa Surakarta. A total of 32 venous blood samples were examined using both anticoagulants. Data were analyzed statistically using the Mann–Whitney test. Results: The mean ESR value in samples with EDTA anticoagulant was 18.3 mm/h, while that in samples with 3.8% sodium citrate was 13.1 mm/h. Statistical analysis yielded a p-value of 0.014 (p < 0.05), indicating a significant difference between the two groups. This difference may be attributed to the chemical properties and osmolarity of each anticoagulant, which affect erythrocyte rouleaux formation. Conclusions: The type of anticoagulant significantly affects ESR results. 3.8% sodium citrate remains the preferred anticoagulant for the Westergren method according to standard protocols, without the addition of 0.86% NaCl dilution